Pengaruh Fraud Pentagon dan Asimetri Informasi terhadap Fraudulent Financial Statement dengan Kualitas Laba Sebagai Pemoderasi - Muhammad Taufiq Arrahman; Nera Marinda Machdar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to examine the influence of pentagon fraud and information asymmetry on fraudulent financial statement with earnings quality as a moderating variable. This study uses a literature review method. The theories underlying this study are agency theory and positive accounting theory. The results of the study show that the factors that influence fraudulent financial statements are pressure, opportunity, rationalization, competence, arrogance, and information asymmetry. Earnings quality can strengthen or weaken the influence of these factors. This study was conducted to enable subsequent researchers to gain a deep understanding of the theories and research results that are relevant to their research topic.